Spray-drying encapsulation of sunflower pollen peptides using carbohydrate polymers: Physicochemical, antioxidant, structural and morphological analysis - Amir Akbarmehr; Seyed Hadi Peighambardoust; Leila Pourhasan; Khashayar Sarabandi (Carbohydrate Polymer Technologies and Applications)
Flower pollen collected by honey bees is a rich source of bioactive peptides (BPs). Different carriers such as maltodextrin (MD), gum Arabic (GA), and β-cyclodextrin (βCD) and their combinations were used for encapsulation of BPs from sunflower pollen protein (SPP). Different physicochemical, antioxidant, functional, structural and morphological properties of the obtained microparticles were evaluated. The amino acid composition of SPP and the derived peptides revealed a high proportion of hydrophobic (∼40%), antioxidant (∼18%), and essential (∼31%) amino acids, indicating their biological potential. Among the microencapsulated samples, the MD-βCD composition exhibited the highest production efficiency (∼65%) and improved physicochemical properties, such as microbial stability, density, flowability, wettability, and solubility, compared to the spray-dried free peptides (free SD-BPs) without a carrier. The encapsulation process helped to maintain the structural integrity of the microparticles and reduced moisture absorption. The SPP-derived peptides encapsulated in MD-βCD also demonstrated potent antioxidant activity, inhibiting ABTS+ (∼75%) and DPPH- (∼69%) free radicals. The results suggest that the BPs obtained from sunflower pollen can be a valuable ingredient for enriching various food products due to their favorable nutritional, functional, and antioxidant properties.